The Influence of Leadership, Communication, Disclosure of Information, and Risk Management on Project Governance in Infrastructure Projects with Project Complexity as a Moderating Variable - Fathoni, Hasful Anwar; Gabriel, Djoko Sihono; Nurcahyo, Rahmat (International Journal Labs, 2025)
Project governance is a critical component in the success of construction and infrastructure projects, particularly in complex environments. This study aims to analyze the influence of effective leadership, communication effectiveness, disclosure of information, and risk management capability and experience on project governance in Indonesia, while also examining the moderating role of project complexity. Using a quantitative approach with Partial Least Square Structural Equation Modelling (PLS-SEM), data were collected through questionnaires from project professionals involved in construction projects. Results indicate that effective leadership, communication effectiveness, risk management capability and experience, and project complexity significantly influence project governance. However, disclosure of information did not show a significant impact. Furthermore, the moderating effect of project complexity on the relationships between effective leadership and project governance, as well as communication effectiveness and project governance, was found to be insignificant. These findings suggest that while project complexity directly affects governance, it does not strengthen or weaken the impact of leadership and communication on governance outcomes in this context. The study contributes a comprehensive empirical model integrating organizational, human, process, and technical factors affecting project governance and highlights the need for targeted leadership and communication strategies to enhance governance effectiveness. This research offers practical insights for improving transparency, accountability, and sustainability in project governance within Indonesia’s construction sector.